What Do Textbooks Talk About? the Problem of Identifying Referents [¿De Qué Hablan Los Libros de Texto? el Problema de la Identificación de Los Referentes] - Hernandez-Silva, C (Centro de Estudos Educacao e Sociedade, 2014)
We show the result of our research on the didactic function of textbooks written in the context of the new curriculum "Science for all". We have been interested in analyzing the relationship between text and inscriptions to identify a) the type of referents that they build and their suitability (the case of waves ) and b) the teaching sequence in the textbook and its possible relation to the learning cycle.